Theoretical Analysis of Reactions in the Knee Joint Caused by Impact - Lindbeck, L. (Engineering Transactions, 1978)
A theoretical model is described, which makes it possible to estimate the impulsive reactions in the knee joint, when an impact is given to the lower leg, e.g. by kicking a ball. The leg is represented as a double pendulum and its impulsive motion is treated by means of Lagrange's equations. It is shown how the impact impulses parallel and perpendicular to the contact tangent of the joint are determined from the angular velocities before and after the impact. As an example a few film sequences are numerically treated.